Evaluation of cellular and physiological alterations of cells from Mytilus galloprovincialis exposed to benzisothiazolinone - Federica Impellitteri; Kristian Riolo; Giorgia Zicarelli; Miriam Porretti; Cristiana Roberta Multisanti; Giuseppe Piccione; Alessia Giannetto; Caterina Faggio (Ecotoxicology and Environmental Safety)
Benzisothiazolinone (BIT) is a preservative and antimicrobial agent widely used in various household and industrial products. It is readily detectable in pesticides, polishes, printing inks and detergents. This extensive use is reflected in a vast amount of this compound in the environment, which may cause toxic effects in organisms that come in contact with it. In light of the aforementioned context, this work aims to investigate the potential cellular and physiological impact on aquatic organisms through in vitro tests, utilising haemocytes and digestive gland (DG) cells derived from the Mediterranean mussel (Mytilus galloprovincialis). Two different concentrations (B1: 0.03 µg/L; B2: 0.3 µg/L) were tested at two different times of exposure (T1: 1 h; T2: 3 h) to evaluate the viability of cells, the phagocytic activity (haemocytes), the regulation volume decrease (RVD on DG cells) capability. Moreover, the cytoprotective mechanisms related to oxidative stress and detoxification were evaluated through the expression analysis by qPCR of key genes involved in these pathways. The most significant results obtained from these tests were the reduction of viability of haemocytes at T2 of exposure to B2, a decrease of vitality in DG cells exposed to B1 during the T1, the significant alteration in the phagocytosis activity, the upregulation of Cu/ZnSOD gene, the inhibition of the CYPY1 gene expression and upregulation of the Heat shock protein 70 (Hsp70) gene following the BIT exposure. These findings provide a valuable foundation for further investigation, offering insights into the potential impact of BIT on aquatic communities.